2022
DOI: 10.3390/biomedicines10112882
|View full text |Cite
|
Sign up to set email alerts
|

Individualization of Mycophenolic Acid Therapy through Pharmacogenetic, Pharmacokinetic and Pharmacodynamic Testing

Abstract: Mycophenolic acid (MPA) is a widely used immunosuppressive agent and exerts its effect by inhibiting inosine 5′-monophosphate dehydrogenase (IMPDH), the main regulating enzyme of purine metabolism. However, significant unexplained differences in the efficacy and tolerability of MPA therapy pose a clinical challenge. Therefore, broad pharmacogenetic, pharmacokinetic, and pharmacodynamic approaches are needed to individualize MPA therapy. In this prospective cohort study including 277 renal transplant recipients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…In lung cancer cells, the expression of CES2 was increased by GDNT with/without MMF but was not significantly affected in the presence of MMF alone. MPA can target IMPDH which has been confirmed to be highly expressed in many tumors [44,45]. In this study, the results of Western blot revealed that both IMPDH1 and IMPDH2 expressions were down-regulated by MMF in the cells, which was further strengthened by GDNT.…”
Section: Fig 5 Ces2 Knockdown Reversed the Synergistic Effect Of Gdnt...mentioning
confidence: 53%
“…In lung cancer cells, the expression of CES2 was increased by GDNT with/without MMF but was not significantly affected in the presence of MMF alone. MPA can target IMPDH which has been confirmed to be highly expressed in many tumors [44,45]. In this study, the results of Western blot revealed that both IMPDH1 and IMPDH2 expressions were down-regulated by MMF in the cells, which was further strengthened by GDNT.…”
Section: Fig 5 Ces2 Knockdown Reversed the Synergistic Effect Of Gdnt...mentioning
confidence: 53%
“…Underdosing can result in organ rejection, and overdosing can result in bone marrow suppression and an increased risk of infections. Therefore, therapeutic drug monitoring for MPA and its major metabolite MPAG is needed (Seyfinejad & Jouyban, 2021; Winnicki et al., 2022).…”
Section: Commentarymentioning
confidence: 99%
“…All calibrators are stable for 6 months when stored below -5°C. (Ferreira et al, 2020;Winnicki et al, 2022). Due to its superior anti-rejection profile, MPA has primarily replaced azathioprine in organ transplantation (Ferreira et al, 2020;van Gelder et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation